Targeted metabolite analysis and antioxidant potential of rumex induratus - Guerra, Luís (2010)
Targeted metabolite analysis of aqueous extract of Rumex induratus leaves, in terms of phenolic compounds and organic acids, and the study of its antioxidant activity against the DPPH• radical, a reactive oxygen species, hypochlorous acid, and a reactive nitrogen species, nitric oxide (•NO), were performed. The samples were collected in several locations, spontaneously occurring or from greenhouse culture, at different stages of development and seasons. The phenolic composition was achieved by high-performance liquid chromatography (HPLC)-diode array detection, and four hydroxycinnamic acid derivatives and 10 flavonoid glycosides (C- and O-heterosides) were determined. Organic acids composition was established by HPLC-UV, revealing five compounds. The total amount of phenolic compounds and organic acids were affected by growing conditions and developmental phase. The aqueous extract exhibited a doserelated activity against all tested reactive species.